Eventide - Hickman, Tracy (Hickman, Tracy. Tales of the dragon's bard, 2012)
When a traveling bard stumbles into a dragon's den, he is forced to tell it stories or be eaten. When he runs out of stories to tell, he makes a deal: if allowed to leave, he promises to return with more tales of adventure, romance, and bravery.